2018
DOI: 10.1590/1678-4162-9775
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de nutrientes, comportamento ingestivo e desempenho de ovinos alimentados com fenos de gramíneas tropicais em diferentes intervalos entre cortes

Abstract: Consumo de nutrientes, comportamento ingestivo e desempenho de ovinos alimentados com fenos de gramíneas tropicais em diferentes intervalos entre cortes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
3
1
1
Order By: Relevance
“…That is, the higher the NDF content, the lower the total intake. The DMI was lower than the 3.62% of LW observed by Pereira et al (2018), for sheep in feedlot fed hay of Massai grass. The highest intake obtained by the authors was a result of the use of a protein concentrate, which allows an additive effect on total intake (Mabrouk et al, 2008).…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…That is, the higher the NDF content, the lower the total intake. The DMI was lower than the 3.62% of LW observed by Pereira et al (2018), for sheep in feedlot fed hay of Massai grass. The highest intake obtained by the authors was a result of the use of a protein concentrate, which allows an additive effect on total intake (Mabrouk et al, 2008).…”
Section: Discussioncontrasting
confidence: 54%
“…Although the highest CP concentration in the leaf was observed in the Aruana grass cultivar, the lower intake of this component by the animals in this cultivar made the CPI intermediate between Marandu and Massai grasses. Pereira et al (2018) observed CPI of 0.48% LW in sheep fed with Massai hay and concentrated in the ratio (2:1). The difference in intake between the studies can be attributed to the use of concentrated supplements.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…A mandioca, pelo seu potencial de produção de carboidratos em suas raízes e de proteína em sua parte aérea, é uma alternativa promissora como ingrediente para a formulação de rações destinadas à alimentação de bovinos (FERNANDES et al, 2021), caprinos (DAVID et al, 2020), ovinos (PEREIRA et al, 2018), aves (LEI et al, 2017) suínos (DIARRA et al, 2017), dentre outras espécies, podendo substituir parcial ou totalmente o milho e o farelo de soja, com redução nos custos de produção. Além de gerar renda adicional para as indústrias processadoras e para os produtores de mandioca, considerando, que a arte aérea, atualmente é um subproduto da produção.…”
Section: Introductionunclassified
“…Ferreira et al, 2014). Haymaking preserves food quality, allowing animal weight gain during the dry period (Pereira, Lima, Assis, & Emerenciano, 2018).…”
Section: Introductionmentioning
confidence: 99%